Diagnosis and rehabilitation of deep wound infection and internal fixation rejection in elbow: A case report. Issue 23 (June 2016) - Lu, Huiping; Song, Lin; Lin, Ying
Abstract : Abstract: This study aims at diagnosis and rehabilitation of a rare case of deep wound infection and internal fixation rejection in elbow. The patient sustained a distal fracture in the humerus 1 year ago, which was internal fixed. The wound always effused and the elbow had pain and swelling; joint motion was limited. Blood sedimentation rate and C reactive protein level increased, bacterial culture suggested deep wound infection, and ultrasound indicated inflammation. The main diagnoses were deep wound infection and internal fixation rejection. Therapeutics interventions were antibiotic agents, physical therapy, operative debridement, incision, drainage, and exercise and physical therapy. One year later, the internal fixation was taken out. His elbow was fully mobilized and the fracture healed. He got back to his former job. When encountered deep wound infection again and again after internal fixation, rejection should be considered. Except for anti-infection treatment, rehabilitation cannot be neglected, or the healing process may be delayed.